Promoción Del Programa De Salud Prenatal Para Disminuir La Alta Incidencia De Niños Prematuros En El Hospital Gineco-Obstétrico Enrique C. Sotomayor De Guayaquil - Soledispa Pisco, Mariana (2011)
The premature´s children number, is found at alarming level in Ecuador, in the year 2008 there was 206.215 birth in our country, in which the 13% and15% were premature (26.000children), at the same time this situation was observed at the hospital gineco obstetric “Enrique C. Sotomayor” which statistics shows the 24.701 birth registered in the 2010, 3631 were premature birth (14.7% of the total birth). The objective of this research is “to determinate the contribution of the promotion of the prenatal health program in the reduction of the high incident of the premature children in the hospital gineco obstetric “Enrique C. Sotomayor” of Guayaquil, in the 2010. The prevention which provides knowledge to mothers in gestation process, helps with the diminution of premature birth, and in this way, it will give to the society the improvement of health level to everyone. The principal goal is to create conscience, about the problem of the premature birth in the country. At the same time, promoting the importance of pregnancy control and the direct relation between the complications and the number of weeks without medical attention. Once preformed the camp research, based on surveys , it was able to verified the research hypothesis , which express the promotion of the prenatal health program would promote at the diminution of the high incident of premature children at the hospital gineco obstetric “Enrique C Sotomayor” of Guayaquil in the 2010, which diagnostics is that pregnant women ; adolescents and mothers don´t have the sufficient knowledge an neither realize the controls in an opportune way in order to get a premature pregnant prevention. For this reason, it´s formulated as proposal the massing of the health educational program for the adolescent pregnant girls and mothers of surrounding areas near the hospital gineco obstetric “Enrique C Sotomayor” in order to reduction of the incident of the premature pregnant including the capacitation and counseling of the users with risk potential in the reproductive sexual health matter, its promotion through the missive’s information way, organization of the club for pregnant women, health fairs, pregnant women meeting , educational mural designs. We hope the research results, reduce the percentage of premature birth, reduce teens pregnancy, strengthen the culture´s level and knowledge of women in reproductive sexual health.